Penguatan Karakter Islami melalui Permainan Edukatif di Pondok Pesantren Aisyah Lampung - Asep Bambang Susanto; Munawaroh; Seka Andrean; M. Arie Wibowo; Anisa Fitri; Shofie Athalia Samsul; Rima Sofiantika (BALE LITERASI, 2026)
This community service activity aims to strengthen the instillation of Islamic character values in students through a fun and interactive learning approach. The background to this activity is the importance of fostering Islamic character in the younger generation, particularly in Islamic boarding schools, and the need for more creative learning methods so that moral values can be understood and internalized more effectively by students. Currently, the character development process is often carried out through conventional material delivery, so an alternative approach is needed to increase student participation and involvement in learning activities. The implementation method for this activity is carried out through several stages: (1) preparation and coordination with the Aisyah Lampung Islamic Boarding School, (2) delivery of material on the importance of Islamic character in daily life, (3) implementation of educational games designed to instill character values such as honesty, cooperation, responsibility, and discipline, and (4) evaluation of the activity to assess participant responses and engagement throughout the activity. This activity involved lecturers and students as activity facilitators, and the students as the main participants. The results of the activity showed that the students participated enthusiastically and demonstrated active participation throughout the process. Through a combination of material delivery and educational games, students not only gain an understanding of Islamic character values but also are able to practice them directly in group activities. Furthermore, these activities create a more enjoyable learning environment and foster a sense of togetherness among students. Therefore, this activity is expected to become an alternative learning method to strengthen Islamic character in students within Islamic boarding schools.